2017
DOI: 10.1021/acs.joc.7b00026
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Diels–Alder Reaction between 3-Vinylindoles and Methyleneindolinone without and with the Assistance of Hydrogen-Bonding Catalyst Bisthiourea: Mechanism, Origin of Stereoselectivity, and Role of Catalyst

Abstract: The Diels-Alder reaction between 3-vinylindoles and methyleneindolinone can proceed both under catalyst-free conditions and with bisthiourea as the catalyst. The reaction with bisthiourea is much faster and results in higher stereoselectivity of the product. The reaction mechanism, origin of stereoselectivity, and role of the catalyst were elaborated based on quantum mechanical calculations and theoretical methods of reactivity indices, NCI, QTAIM, and distortion/interaction models. In the uncatalyzed reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 88 publications
(117 reference statements)
0
10
0
Order By: Relevance
“…On the basis of the above results and the previously reported reactions, , a plausible domino reaction mechanism is relationally proposed in Scheme by using 3-phenacylideneoxindoline as the substrate. At first, a 3-alkenylindole ( A ) was generated by the Friedel–Crafts reaction of indole and acetophenone with dehydration in the presence of triflic acid.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the above results and the previously reported reactions, , a plausible domino reaction mechanism is relationally proposed in Scheme by using 3-phenacylideneoxindoline as the substrate. At first, a 3-alkenylindole ( A ) was generated by the Friedel–Crafts reaction of indole and acetophenone with dehydration in the presence of triflic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the global electrophilicity index ω is measured by ω = (μ 2 /2η). The empirical (relative) nucleophilicity index , N taking the HOMO energy of tetracyanoethylene (TCE) as a reference was defined as N = E HOMO(R) – E HOMO(TCE) by Domingo and co-workers, which was calculated basing on the HOMO energies of reactants. The HOMO and LUMO orbital energy, electronic chemical potential (μ), chemical hardness (η), electrophilicity (ω), and nucleophilicity ( N ) indices for reactants ( R1 , R2 ) are listed in Table , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Materials), which might influence the kinetics of the model systems by hydrogen bonding (HB) interactions. Several studies have demonstrated that strong or bifunctional hydrogen bonds are capable of catalyzing the Diels–Alder cycloaddition reaction and may even alter the preference for endo versus exo [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%